Penerapan Metode Pembelajaran Berbasis Masalah Terhadap Hasil Belajar Fisika Siswa - Kholida Ismatulloh; Ropikoh Ropikoh (Kappa Journal, 2022)
A research has been conducted entitled the application of problem-based learning methods to the physics learning outcomes of class VIII students at SMPN 3 Selong. This study aims to see whether there is an effect of problem-based learning methods on student learning outcomes in the subject of motion in class VIII SMPN 3 Selong. This type of research is quantitative by measuring learning outcomes from the post test results given at the end of the lesson. The population used in this study was class VIII, which amounted to 320 people with a total sampling technique method of taking only two classes, namely class VIII D as the control class and class VIII E as the experimental class. The research hypothesis was carried out using the t-test with the results obtained  = 5.023>  = 1.763 using a significant level of 5%. With this, the conclusion is  rejected